Model Simulation of Holiday Session Traffic Flow at Three Ways Intersection in Indonesia - Aryahito, Faqih Oki; Wihardi, Rendy Yogista; Marunda, Muhammad Azka; Hariani, Mira Lestira (PT FORMOSA CENDEKIA GLOBAL, 2025)
Traffic density increases fluctuatively during holidays due to rising tourist activities, requiring seasonal traffic management. This study analyzes the impact using PKJI 2023 and PTV VISSIM modeling. At peak hour, the intersection shows a degree of saturation (DS) = 0.776 and average delay = 13.075 sec/MPH with LOS B. Projections for the next 5–10 years indicate DS = 1.10 and delay = 25.234 sec/MPH with LOS D. Of three modeled alternatives, the best is Alternative 2: diverting major north-south traffic to the east minor road, resulting in average speed = 23 km/h, delay = 14.075 sec/MP, queue length = 16.417 m, and LOS B.